Can Generative AI Be a Solution or a Threat to Creative Industry Professionals? Assessing Readiness with the Rasch Model - Rizal Furqan Ramadhan; Sultan Ahmad; Nafae Mohnna Alanazi; Korhan Cengiz (Blockchain, Artificial Intelligence, and Future Research, 2026)
This study examines the readiness of creative industry professionals, specifically in photography and filmmaking, to adopt Generative AI (GenAI) technologies, utilizing the Rasch Model to assess their perceptions, technological self-efficacy, and concerns about job displacement and ethical implications. A survey was conducted with 2,424 professionals across different continents, revealing that younger professionals and those from technologically advanced regions are more ready to adopt GenAI, while older professionals show greater resistance due to concerns about creative control and job security. The study found significant differences in readiness across job roles, with photographers more willing to embrace AI for routine tasks, while filmmakers and editors expressed more hesitations regarding the ethical and creative challenges posed by AI. The research contributes to the literature by offering a psychometrically rigorous assessment of readiness for GenAI adoption, introducing Differential Item Functioning (DIF) analysis to explore demographic variations, and providing practical recommendations for the creative industries on how to manage the integration of AI technologies. The findings emphasize the importance of tailored interventions, organizational support, and reskilling initiatives to successfully integrate AI into creative workflows while preserving human creativity.